Creative Methods for Creativity Research(ers)? Speculations. Issue 1 (March 2022) - Koro, Mirka; Tanggaard, Lene
Creativity forms a part of educational curriculum and is an important element of education research. Clearly, creativity research of the past has made a great impact in the ways in which creativity has been integrated within education and educational practice. Yet how creativity has been studied and how the methodologies of these studies shape produced knowledge and impact educational practice are still rather limited and limiting. This chapter calls for methodological experimentation, various forms of performativity, and creativity in the context of research utilizing speculative wonderings. We situate our arguments in different trends in creativity research and discuss more methodologically diverse, speculative, and creative futures.